Six-year retrospective review of drug reaction with eosinophilia and systemic symptoms - Pranee Wongkitisophon (2018)
Drug reaction with eosinophilia and systemic symptoms (DRESS) is a rare, severe adverse drug reaction. The aim of this study was to characterize the aetiology, clinical features, laboratory findings, and management of patients with DRESS, diagnosed from January 2005 to April 2010 in a tertiary centre in Thailand. Twenty-seven patients were included in the study with a mean age of 52 years. Phenytoin, allopurinol, and nevirapine were the most commonly implicated medications. Mean duration of drug administration before the onset of symptoms was 34 days. The latent period was longer for allopurinol (103 days) and shorter for nevirapine (10 days). Skin rash was seen in all patients, while fever and lymphadenopathy were found in 88.9% and 22.2%, respectively. Hepatic and haematological involvement were the two most common systemic complications, occurring in 96.3% and 85.2%, respectively. Most patients were treated with systemic corticosteroids, for a mean duration of 49 days. The mortality rate in this study was 3.7%. Early detection and discontinuation of the suspected drug are the key steps of management. © 2012 The Authors.